Potassium Supplying Capacity of Some Citrus Orchard Soils in Foothill Himalayas through Quantity-Intensity Approach - and Sanjay Arora, Seema Sharma, Vikas Sharma (Journal of the Indian Society of Soil Science, 2018)
Assessment of soil potassium (K) through commonly used extractants like ammonium acetate may not be sufficient to assess the long-term K supplying capacity of the soils. We undertook a study to assess the K supplying capacity of citrus orchard soils in the sub-montane region of foothill Himalayas, through quantity-intensity approach. Equilibrium activity ratio of K (ARek) in citrus orchard soils ranged from 1.10 × 10-3 to 5.60 × 10-3 (mole L-1)0.5. The ARek was significantly and positively correlated with available forms of K, KL (labile K) and DK0 (K held on K-specific sites) and negatively correlated with –DG (free energy of exchange). The potential buffering capacity of K (PBC0k) of the soils was 36.5 to 90.7 cmol(p+) kg-1/(moles L-1)0.5 with mean value of 62.7 cmol(p+)kg-1/(moles L-1)0.5. The PBC0k was positively correlated with –DG and KG × CEC (product of Gapon selectivity coefficient and cation exchange capacity). These relations indicate that soils having higher affinity for K adsorption will need higher free energy for the exchange reaction and will thus resist abrupt changes in K concentration. The DK0, KX (K on non-specific sites) and KL values for these soils varied from 0.090 to 0.234, 0.006 to 0.349 and 0.114 to 0.527 cmol(p+)kg-1 of soil, respectively. Both KL and KX also showed a positive correlation with different forms of K and K saturation percentage. Free energy of exchange values were in the range of 12.84 to 16.88 KJ mol-1, and had a significantly negative relationship with available forms of K, with the values suggesting that majority of the soils are either deficient or on threshold of deficiency. The KG values varied from 2.5 to 10.1 (L mol-1)0.5. Leaf K was negatively and significantly correlated with KG.